TAFSIR TARBAWI: PENDIDIKAN ANTI KORUPSI DALAM ISLAM - Ibnurawandhy N. Hula; Mariaty Podungge; Elvia Safia; Fingki Daaliuwa (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
The large number of corruption that occurred in Indonesia is the background of this research. The problem that is the focus of this research study is how anti-corruption education in Islam, and how to introduce anti-corruption education from an early age to society such as honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage and justice. The purpose of this research is to find out anti-corruption education in Islam which is contained in the verses of the Qur'an. In this case, the author will focus on one verse, which is contained in QS Al-Baqarah (2): 188 regarding the prohibition of eating wealth in a vanity way. This type of research is a literature review, and the techniques used in collecting data in this study are using primary and secondary data sources. The results of this study found that one of the factors that causes corruption is due to the implementation of anti-corruption education from an early age which is rarely carried out by the community. This is due to the still weak integrity and self-awareness of a number of officials and some of the community itself. In conclusion, if anti-corruption seeds are instilled in students from the start, then the attitude of resistance to corrupt behavior will strengthen and strengthen the resistance movement against corruption.Keywords:Education, Anti Corruption, Tarbawi interpretation